Paul the Apostle : his life and legacy in their Roman context - Harrill, James Albert, 1963- (Cambridge ; New York : Cambridge University Press, 2012)
"This book is a controversial new biography of the apostle Paul that argues for his inclusion in the pantheon of key figures of classical antiquity, along with the likes of Socrates, Alexander the Great, Cleopatra, and Augustus"--
1. THE PROBLEMS AND POSSIBILITIES OF PAUL'S LETTERS COLLECTED INTO A SINGLE CORPUS2. MARCION AND VALENTINUS: TWO PAULINE RIVALS AT ROME; The Gnostics and Valentinus; 3. IRENAEUS OF LYONS: THE RULE OF FAITH AND AN UNORIGINAL PAUL; 4. ORIGEN OF ALEXANDRIA: THE HISTORICAL PAUL REAPPEARS; 5. JOHN CHRYSOSTOM: PAULINE INCONSISTENCY AS THE WISE PHYSICIAN; 6 HOW THE WEST GOT PAUL WRONG; 1. THE APOSTLE OF LIGHT: A MANICHAEAN PAUL; 2. LOST IN TRANSLATION: THE FIRST LATIN COMMENTARIES ON PAUL; 3. THE APOSTLE OF FREE WILL: PELAGIUS'S PAUL.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Paul, -- the Apostle, Saint; Paul, -- the Apostle, Saint; HISTORY -- General; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; RELIGION -- Biblical Biography -- New Testament; Romeinse oudheid; Receptie; Electronic books; Biografieën (vorm)